2018
DOI: 10.5713/ajas.18.0283
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Indonesian Cattle Breeds Based on Microsatellite Markers

Abstract: All identified alleles in this study were able to classify the cattle population into three clusters i.e. Bos taurus cluster (Simmental Purebred, Simmental Crossbreed, and Friesian Holstein cattle); Bos indicus cluster (Sumba Ongole, Ongole Grade, Madura, Pasundan, and Pesisir cattle); and Bos javanicus cluster (Banteng and Bali cattle).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 27 publications
4
28
0
6
Order By: Relevance
“…In general, the levels of heterozygosity (H e and H o ) that were observed in this study are similar to previous reports (Agung et al, 2019;Egito et al, 2007;Freeman et al, 2004;Suh et al, 2014;Zhao et al, 2017). Given that these observed levels of heterozygosity were greater than 0.5, this indicates that the 10 microsatellite markers are suitable for genetic diversity studies in the three dairy breeds (Sheriff & Alemayehu, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the levels of heterozygosity (H e and H o ) that were observed in this study are similar to previous reports (Agung et al, 2019;Egito et al, 2007;Freeman et al, 2004;Suh et al, 2014;Zhao et al, 2017). Given that these observed levels of heterozygosity were greater than 0.5, this indicates that the 10 microsatellite markers are suitable for genetic diversity studies in the three dairy breeds (Sheriff & Alemayehu, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, microsatellite markers are used for identification of parental lineages (Erhardt & Weimann, 2007), mapping genes for economically important traits (Goddard & Hayes, 2007;Naicy, 2008), and aiding in marker-assisted selection (MAS) (Oltenacu & Broom, 2010;Schefers & Weigel, 2012). Microsatellites have been commended for use in genetic diversity studies because of their accuracy, versatility, abundancy and being spread over the entire genome (Agung et al, 2019;Erhardt & Weimann, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Previously wide studies on buffalo domestication have been conducted and it was concluded that the origin of buffalo domestication occurred in China (Yue et al, 2013). Microsatellites have been widely used for the study of genetic diversity on various types of livestock in Indonesia such as in cattle (Abdullah et al, 2012;Agung et al, 2016;Agung et al, 2019), goats (Zein et al, 2012), and sheep (Jakaria et al, 2012). Microsatellite studies in local swamp buffaloes have been reported in Indonesia, but are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate methods can summarize the genetic variability without making assumptions about an evolution model, the absence of linkage disequilibrium, and it does not rely on Hardy-Weinberg equilibrium [7]. Principal Component Analysis (PCA) is a multivariate method used in analyzing microsatellite data on Indonesian animal genetic resources and is able to distinguish between species of cattle [8]. The purpose of this study was to examine several multivariate methods in classifying genetic diversity, especially in Indonesian chickens and provides recommendations of multivariate methods that can be used to see genetic differences based on allele frequency data.…”
Section: Introductionmentioning
confidence: 99%